Analisis Fungsi Jasa Bio-Ekologis Hutan Kota Kawasan Industri - Syihabuddin, Akhmad; Darmadi, Budi; Waryono, Tarsoen (Bumi Lestari; Vol 20 No 1 (2020)DO - 10.24843/blje.2020.v20.i01.p01, 2020)
The construction of green areas in the form of urban forests around the industrial area on the belief Pulogadung role bio-ecological service, functions of various types of plant communities is considered capable of improving the environmental quality of industrial estates. The purposes of study: (1) analyze the dynamics of the urban forest tree growth; (2) analyze the micro-climatic conditions; (3) to analyze the carbon stored amount; (4) analyze the knowledge and attitudes; and (5) urban forest management analyze the industrial area. The study was conducted in Urban forest Industrial Estate Pulogadung, East Jakarta. Samples of vegetation consist of three single swath, while human sample consisted of 40 respondents and two informants. The structure and composition of vegetation that dominates in the Urban forest Industrial Estate Pulogadung Samanea saman for phase trees with IVI 67.68%; Swietenia mahagoni for phase pole with IVI 241.846%; Leucaena leucocephala for phase stake with IVI 126.13%. The growth dynamics of urban forest tree unnatural. Micro-climatic conditions in the category uncomfortable are 29.75, whereas the condition ideally convenient in the range 25.0 - 27.0°C. The amount of carbon stocks in urban forest Industrial Estate Pulogadung of 77.27 tons/ha, while the average carbon density per hectare is 283.3 tons/ha. People's knowledge of the existence of the benefits of urban forests Industrial Estate Pulogadung as a producer of oxygen is greater (97.5%) of the thermostat (90%), and infiltration of rainwater (82.5%), while public attitudes as much as 83.75% agree to participate in managing the urban forest Industrial Estate Pulogadung.